2016
DOI: 10.1007/jhep11(2016)136
|View full text |Cite
|
Sign up to set email alerts
|

Gravity on-shell diagrams

Abstract: We study on-shell diagrams for gravity theories with any number of supersymmetries and find a compact Grassmannian formula in terms of edge variables of the graphs. Unlike in gauge theory where the analogous form involves only d log-factors, in gravity there is a non-trivial numerator as well as higher degree poles in the edge variables. Based on the structure of the Grassmannian formula for N = 8 supergravity we conjecture that gravity loop amplitudes also possess similar properties. In particular, we find th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 125 publications
(249 reference statements)
0
80
0
Order By: Relevance
“…Therefore, cuts are well-defined functions whose analytic properties can be analyzed without any difficulties. Iterative use of the cut procedure leads to elementary objects called on-shell diagrams [25] which were also studied in the gravity context [26,27]. In [26] we found that gravity on-shell diagrams exhibit some surprising features in the collinear regions and as a application we found a direct link to the mild IR singularities in gravity amplitudes.…”
mentioning
confidence: 75%
“…Therefore, cuts are well-defined functions whose analytic properties can be analyzed without any difficulties. Iterative use of the cut procedure leads to elementary objects called on-shell diagrams [25] which were also studied in the gravity context [26,27]. In [26] we found that gravity on-shell diagrams exhibit some surprising features in the collinear regions and as a application we found a direct link to the mild IR singularities in gravity amplitudes.…”
mentioning
confidence: 75%
“…Even though they have been most prominently featured in the realm of supersymmetric theories [21,[129][130][131][132][133] (see e.g. [134,135] for some exceptions), they can generally be defined from first principles without reference to (off-shell) loop integrands in any quantum field theory.…”
Section: Jhep06(2017)059mentioning
confidence: 99%
“…There does not yet exist any truly satisfactory approach to the computation of general on-shell functions in SUGRA. Although (as with all massless quantum field theories in four dimensions) there exists suggestive representations of on-shell functions in terms of Grassmannian integrals [94], the actual expressions found for leading singularities in SUGRA still surprise us with their simplicity.…”
Section: B2 Two-loop Leading Singularities Of Mhv Amplitudes In Sugramentioning
confidence: 99%